Fructosamine is a useful indicator of hyperglycaemia and glucose control in clinical and epidemiological studies--cross-sectional and longitudinal experience from the AMORIS cohort. - Håkan Malmström; Göran Walldius; Valdemar Grill; Ingmar Jungner; Soffia Gudbjörnsdottir; Niklas Hammar (PLoS ONE, 2014)
CONTEXT: Fructosamine is a glycemic biomarker which may be useful for indication and control of diabetes respectively. OBJECTIVE: The objective of the study was to evaluate fructosamine as an indicator of hyperglycaemia and glucose control in subjects with diabetes. DESIGN, SETTING & PATIENTS: From the AMORIS cohort, subjects with serum glucose, fructosamine and HbA1c from the same examination were studied cross-sectionally and longitudinally (n = 10,987; 5,590 overnight-fasting). The guidelines of the American Diabetes Association were followed for classification of prediabetes and diabetes. Separate analyses were performed in patients with a newly detected or a known diagnosis of type 1 or type 2 diabetes respectively. RESULTS: All three biomarkers were strongly correlated. With regard to the association between fructosamine and HbA1c Pearson linear correlation coefficients in the range of 0.67-0.75 were observed in fasting and non-fasting subjects with type 1 or type 2 diabetes. Analyses of glucose control in fasting patients with type 2 diabetes having all three biomarkers measured at three separate occasions within on average 290 days of the index examination showed similar trends over time for glucose, fructosamine and HbA1c. Discrimination of subjects with and without diabetes across the range of fructosamine levels was good (area under curve (AUC) 0.91-0.95) and a fructosamine level of 2.5 mmol/L classified subjects to diabetes with a sensitivity of 61% and a specificity of 97%. CONCLUSIONS: Fructosamine is closely associated with HbA1c and glucose respectively and may be a useful biomarker of hyperglycaemia and glucose control in clinical and epidemiological studies.